Perancangan Design Troli dengan Metode Kansei Engginering - Anshory, Rafian Egy; Misrianto, Misrianto; Pratiwi, Septiana Alia; Fadilla, Muhammad Gias Nur; Maria, Ernasti (Fakultas Teknik Universitas Tulang Bawang, 2025)
The application of assistive devices in the world of work does play an important role as well as always being considered. Operators at the PT PLN Tarakan Warehousing Work Unit in Ballikpapan City are experiencing problems in the operation of moving goods. This unit works traditionally with limited road access. The purpose of this research is to design lifting and transporting aids. The sample of this research is employees of the Warehousing Unit by applying purposive sampling technique. This research uses Kansei Engineering (KE) and Exploratory Factor Analysis (EFA) methods. The results illustrate that there are 77 Kansei Engineering Words (KKE) through identification of consumer needs through surveys and interviews. 77 KKE were treated based on similarity or similarity of meaning and obtained 10 KKE. Making questionnaires as many as KKE and then evaluated using the Linkert scale. The results of the questionnaire were tested for validity and reliability, and 50% of the KKE were valid and reliable. Factor analysis used EFA and resulted in 2 factors or stone patterns. The first factor consists of easy to use, strong, safe, and attractive. While the second factor consists of lightweight and attractive. Of the two factors, the second factor was chosen as a reference for designing the trolley design. Keywords : Analysis Factor, Design Trolley, Exploratory Factor Analysis (EFA), Kansei Engineering